Blood pressure control in patients with chronic kidney disease according to office and home blood pressures. Issue 5 (October 2020) - Chantrel, François; Ott, Julien; Dimitrov, Yves; Babici, Daniela; Fourcade, Jacques; Hanon, Olivier; Achard, Jean-Michel; Jabourek, Olivier; Ducher, Michel; Fauvel, Jean-Pierre
Abstract : Objectives: The aim of this study was to assess blood pressure (BP) control in patients with chronic kidney disease (CKD) according to office and home BP and to assess the prevalence of normal BP, white-coat uncontrolled hypertension (WUCH), masked uncontrolled hypertension (MUCH) and elevated BP. Methods: Patients with renal failure with or without proteinuria were included in this multicenter observational study. Office BP was first measured by the physician using a self-monitoring BP device (three automatic readings), then by the patient at home (morning and evening) over 3 consecutive days. WUCH was defined as a systolic BP (SBP)/diastolic BP (DBP) ≥140/90 mmHg in the clinic and SBP/DBP<135/85 mmHg at home. MUCH was defined as SBP/DBP <140/90 mmHg in the clinic and SBP/DBP ≥135/85 mmHg at home. Results: Among the 243 included subjects, data of 225 patients were analyzed. Mean estimated glomerular filtration rate was 37.7 ± 15.7 mL/min/1.73 m 2 and mean office SBP/DBP was 154 ± 19/83 ± 13 mmHg. Mean office SBP/DBP was significantly higher than home SBP/DBP (+9.0 ± 15.1/+7.0 ± 10.0 mmHg, P  < 0.01). Normal BP (office and home BP), WUCH, MUCH and elevated BP (office and home BP) rates were 12.0, 14.2, 6.7 and 67.1%, respectively. The patients were taking, on average, 2.8 ± 1.5 antihypertensive drugs/day. Conclusion: BP control in patients with CKD was poor. Routine use of 'out-of-office' BP measurement, in addition to office BP by which we can identify patients with WUCH or MUCH, should be recommended based on the current findings.